Mechanical Behavior Of Lightweight Concrete Mixed With Bamboo Shavings - Erdiansyah Putra, B (Faculty Of Engineering University 17 August 1945 Semarang, 2023)
The development and progress of science, especially in the field of building materials technology, has encouraged the birth of new concepts, especially for construction made of concrete. One of these new concepts is by presenting innovations in the manufacture of lightweight concrete to reduce the excessive use of bricks / concrete blocks as non-structural building materials such as walls. One way to overcome this is to use lightweight concrete as a precast wall or as a brick. Its use can reduce the magnitude of the load acting on the building and is fast in installation. The purpose of this research on lightweight concrete with a mixture of bamboo shavings is to determine the properties of the stacking material, the relationship between mechanical properties at the age of 14 and 28 days of concrete with no soaking conditions, and the effect of the addition of bamboo shavings. The tests and examinations carried out were compressive strength, strain, and content weight of lightweight concrete. The results showed that lightweight concrete with the most ideal bamboo shavings mixture was 1 cement: 1-1.5 bamboo shavings: 2 sand (fas value: 0.8) has a compressive strength of 1.65 MPa and 1.63 Mpa, respectively, for a content weight of 753.01 kg/m3 and 609.66 kg/m3.